Nursing scientific production on noncommunicable diseases in the elderly: relationships with health needs, research priorities in Brazil and nursing work (Research, Society and Development, 2020)
The objective of this study was to know the Brazilian scientific production of nursing about Noncommunicable Diseases (NCDs) in the elderly, in relation to the health needs of the elderly population, health research priorities, and nursing work. Qualitative, documentary, exploratory-descriptive research in 11 Brazilian journals, classified in CAPES Qualis: "A1", "A2" and "B1", in the area of evaluation "Nursing". Sixty-two articles selected from the theme of NCDs in the elderly were selected from sub-agenda 5 of the National Agenda for Priorities in Health Research. For analysis, we used epidemiological data and health indicators on NCDs, morbidities, hospital admissions. and mortality in the elderly. The studies address the main emerging NCDs in the elderly Brazilian population, except for chronic respiratory diseases. The publications reviewed partially support the agenda's recommendations. The publications recognize the need to explore innovative nursing interventions, but there is a departure from research on the real needs of practice and effective interventions. The study directs a close and focused look from researchers, journal editors and research supporters regarding the real impact of knowledge produced in nursing in gerontogeriatrics and NCDs.